Relatos, trajetórias e imagens: uma etnografia em construção sobre os Ye'pâ-masa do baixo Uaupés (alto rio Negro) - Rodrigues, Raphael (2012)
This study aimed to observe the motivations of an indigenous leader of the Northwest Amazon, Maximilian Menezes, in his desire to produce a written record of the Inapéporã s trajectory and placement of hierarchical, one of about forty clans tukano. From the collection of mythical and historical narratives attempted to recover the trajectory of this group from the river Papuri toward the lower river Uaupes contributing thereby to a greater understanding of the ethno-sociological conformation of this region. The history of the community of Ananás, where Max was born, and where co-lived with another tukano clan, the Sanadepó-porã, was rebuilt, in part, from these oral histories and historical sources, mainly. We tried to observe, from conflicting reports of episodes involving specific movements related to shamanism and scatter some of the groups own dynamic tukano regarding mainly the formation of communities, micro-politics of affinity and co-residence between agnatic groups. This paper revisits classic themes of regional literature as hierarchy, social organization, cosmology, and is constituted as a starting point for research collaboration marked mainly by the fluidity between native and anthropological knowledge.